Mesenchymal Stromal Cell Derived Extracellular Vesicles Reduce Hypoxia-Ischaemia Induced Perinatal Brain Injury - Sisa, Claudia; Kholia, Sharad; Naylor, Jordan; Herrera Sanchez, Maria Beatriz; Bruno, Stefania; Deregibus, Maria Chiara; Camussi, Giovanni; Inal, Jameel M.; Lange, Sigrun; Hristova, Mariya (Frontiers in Physiology, 2019)
Background: Neonatal hypoxic ischemic (HI) insult is a leading cause of disability and death in newborns, with therapeutic hypothermia being the only currently available clinical intervention. Thus there is a great need for adjunct and novel treatments for enhanced or alternative post-HI neuroprotection. Extracellular vesicles (EVs) derived from mesenchymal stromal/stem cells (MSCs) have recently been shown to exhibit regenerative effects in various injury models. Here we present findings showing neuroprotective effects of MSC-derived EVs in the Rice-Vannucci model of severe HI-induced neonatal brain insult. Method: MSC-derived EVs were applied intranasally immediately post HI-insult and behavioural outcomes were observed 48 h following MSC-EV treatment, as assessed by negative geotaxis. Brains were thereafter excised and assessed for changes in glial responses, cell death and neuronal loss as markers of damage at 48 h post HI-insult. Results: Brains of the MSC-EV treated group showed a significant decrease in microglial activation, cell death and percentage tissue volume loss in multiple brain regions, compared to the control-treated groups. Furthermore, negative geotaxis test showed improved behavioural outcomes at 48 h following MSC-EV treatment. Conclusion: Our findings highlight the clinical potential of using MSC-derived EVs following neonatal hypoxia-ischaemia.